The benefits to South African investors from international portfolio diversification using an ex ante investment strategy - N. Bhana (South African Journal of Business Management, 1987)
This investigation uses an ex ante 'buy the market' investment strategy to compare the risk-return characteristics of a South African portfolio with an internationally diversified portfolio representing 18 countries during the 1969 - 1983 period. Without taking differences in risk into consideration, the international portfolio, on average, produced slightly higher annual returns. Furthermore, the South African portfolio produced very erratic returns in comparison with the steady returns attained by the international portfolio. The results also demonstrate the ability of international portfolios to maximize the long-term rate of return, even though many year-by-year returns may be less than the returns from domestic portfolios. The international portfolio has a relative performance which is 3,0387 times that of the South African portfolio when the actual risk associated with the two portfolios are taken into consideration. An international portfolio containing goldmining shares is able to attain relatively high returns without adding to the overall portfolio risk. By contrast a South African investor holding goldmining shares bears a large element of risk which is not diversifiable because of exchange control restrictions. The results of this investigation provide a strong case for international portfolio diversification by South African investors. Furthermore, South African investors are bearing a high cost for the inability to attain effective diversification as a result of exchange control regulations. In view of the public policy implications of foreign security investments, representations should be made to the authorities with the objective of expediting exchange control reform in South Africa.Hierdie ondersoek gebruik 'n ex ante 'koop-die-mark'-belegginstrategie ten einde die risikoopbrengseienskappe van 'n Suid-Afrikaanse portefeulje met 'n internasionaalgediversifiseerde portefeulje verteenwoordigend van 18 lande gedurende die 1969 - 1983 periode, te vergelyk. Sonder inagneming van risikoverskille, blyk dit dat die internasionale portefeulje gemiddeld hoer jaarlikse rendemente gehad het. Boonop het die Suid-Afrikaanse portefeulje wisselvallige opbrengste gelewer in vergelyking met die stabiele opbrengste verkry deur die internasionale portefeulje om langtermyn-opbrengskoerse te maksimeer, selfs al blyk jaar-vir-jaar-opbrengste minder te wees as met huishoudelike portefeuljes. Wanneer die werklike risiko's betrokke in die twee portefeuljes in aanmerking geneem word, was die relatiewe vertoning van die internasionale portefeulje 3,0387 keer die van die Suid-Afrikaanse portefeulje. 'n internasionale portefeulje met goudaandele is in staat tot relatief hoe opbrengste sonder die toevoeging van die algehele portefeuljerisiko's. In teenstelling hiermee, moet die Suid-Afrikaanse belegger 'n redelike groot risiko-element self akkommodeer aangesien wisselkoersbeheerbeperkings diversifikasie uitskakel. Die resultate van hierdie ondersoek verskaf 'n sterk basis vir Suid-Afrikaanse beleggers om betrokke te raak in internasionale portefeuljediversifikasie. As gevolg van wisselkoersbeheermaatreels, moet die Suid-Afrikaanse belegger ook nog die hoe koste vir die onvermoe om effektiewe diversifikasie te inisieer, absorbeer. In die lig van die openbarebeleid-uitkomste van buitelandse sekuriteitsbeleggings, behoort die owerhede versoek te word om bestaande wisselkoersbeheermaatreels spoedig in heroorweging te neem.
Keywords: 650